Synchronous Epithelioid Stromal Tumour and Lipoma in the Stomach - Nabeel Al-Brahim; Jasim Radhi; John Gately (Canadian Journal of Gastroenterology)
An 82-year-old man presented with upper gastrointestinal bleeding. A polypoid lesion of the distal stomach with focal ulceration was seen at endoscopy. This was treated by a partial gastrectomy. The resected stomach contained two separate tumours near the pylorus: a gastrointestinal stromal tumour (GIST) and an adjacent lipoma. The literature includes case reports of synchronously occurring GIST and adenocarcinoma, GIST and mucosa-associated lymphoid tissue lymphoma and GIST and carcinoid tumour. Herein is the first case report of two distinct mesenchymal tumors coexisting in the stomach.